2018
DOI: 10.1080/14786419.2018.1440220
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents from the rhizomes of Polygonatum sibiricum Red. and anti-inflammatory activity in RAW264.7 macrophage cells

Abstract: Chemical investigation of the rhizomes of Polygonatum sibiricum Red. led to the identification of 27 constituents. Among them, a total of 16 compounds were obtained from Polygonatum for the first time, in which, 3 and 4 were also firstly isolated as natural products. Anti-inflammatory activity studies on 13 isolated compounds showed that β-carboline constituents, especially compounds 1 and 2, significantly inhibited the expression of NO, TNF-α, IL-6 and IL-1β in lipopolysaccharide (LPS)-treated RAW264.7 macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…As it contains polysaccharides, saponins, flavones, lignans, amino acids, vitamins, alkaloids, and various trace elements, P. sibiricum is considered to have high medicinal and nutritional values . As recorded in the Compendium of Materia Medica, the efficacy of various parts of P.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it contains polysaccharides, saponins, flavones, lignans, amino acids, vitamins, alkaloids, and various trace elements, P. sibiricum is considered to have high medicinal and nutritional values . As recorded in the Compendium of Materia Medica, the efficacy of various parts of P.…”
Section: Introductionmentioning
confidence: 99%
“…4 As it contains polysaccharides, saponins, flavones, lignans, amino acids, vitamins, alkaloids, and various trace elements, P. sibiricum is considered to have high medicinal and nutritional values. 5 As recorded in the Compendium of Materia Medica, the efficacy of various parts of P. sibiricum used in traditional medicine decreases in the following order: flower > fruit > rhizome. 6 Therefore, in this study, we aimed to comprehensively investigate the underutilized parts of P. sibiricum and its rhizome to increase their usage and reduce waste.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse flavones [ 2 ], homoisoflavanones [ 3 ], alkaloids [ 4 ], steroid saponins [ 5 ], triterpenoid saponins [ 6 ], polysaccharides [ 7 ] and their derivatives were isolated from this species in past studies. Past studies also showed that this herb exhibited anti-aging [ 7 , 8 ], anti-inflammatory [ 9 , 10 ], anti-osteoporotic [ 11 , 12 ], immune enhancing [ 13 , 14 ], neuroprotective [ 15 ], anti-diabetic [ 16 ], anticancer [ 17 ], and sleep-promoting [ 18 ] activities.…”
Section: Introductionmentioning
confidence: 99%
“…Polygonatum sibiricum is a traditional Chinese medicine for renal protection and treating nephropathy (Bibi et al., 2016 ; Cai et al., 2019 ; Zhao et al., 2019 ; Han et al., 2020 ; Wang et al., 2020 ). It has been widely used as a functional food around all Asian countries.…”
Section: Introductionmentioning
confidence: 99%